MELACAK AKAR IDEOLOGI PURITANISME ISLAM: Survei Biografi atas âTiga Abdullahâ - Jinan, Mutohharun (IAIN Walisongo Semarang, 2014)
This paper examined the variant of Islamic movement with biographical point ofview to three muslims figures, namely Abdullah Sungkar (the founder of JemaahIslamiyah), Abdullah Marzuki (the founder of Majelis Pengajian Islam), andAbdullah Thufail Saputro (the founder of Majelis Tafsir Al-Qurâan). They havebeen known as the âTriple Aâ. They have been being very influential in thedynamics of Islam in Surakarta since the 1970s until today. They have workedtogether to spread the teachings of Islam in many religious activities. Applyingqualitative approach and using documentation study, it was founded that due tomany differences in intellectual backgrounds and ideological orientations of eachother that lead them to choose different strategies to realize the ideal Islamicsociety. The first figure selected resistant position and fight against the hegemonyof the state, the second figure chose neutral and do not care about political issues,and the third figure to choose the path of accommodative policy of the state.***Artikel ini membahas tentang varian gerakan Islam di Surakarta dengan pendekatanbiografi tokoh. Tokoh yang dijadikan objek kajian adalah AbdullahSungkar (pendiri gerakan Jamaah Islamiyah), Abdullah Marzuki (pendiri MajelisPengajian Islam), dan Abdullah Thufail Saputro (pendiri gerakan Majelis Tafsir Al-Quran). Tiga tokoh ini dikenal oleh masyarakat dengan sebutan Tiga A. Pemikirandan lembaga mereka sangat berpengaruh dalam dinamika perkembangan dandakwah Islam di Surakarta pada tahun 1970-an hingga sekarang. Mereka pernahbekerja sama dalam lembaga dakwah. Dengan pendekatan kualitatif dan kajiandokumen ditemukan bahwa karenas beberapa perbedaan latar belakang,pandangan, dan orientasi ideologi menjadikan mereka berpisah dan membentukgerakan sendiri-sendiri. Abdullah Sungkar memilih jalur berseberangan dengannegara, Abdullah Marzuki memilih jalur pendidikan pesantren dan tidak berpolitik,sedangkan Abdullah Thufail Saputro memilih jalur akomodasi danbekerjasama dengan negara.Keywords: puritanisme, dakwah Islam, tiga Abdullah, Surakarta